2016
DOI: 10.7717/peerj.1870
|View full text |Cite
|
Sign up to set email alerts
|

Pine polyphenols fromPinus koraiensisprevent injuries induced by gamma radiation in mice

Abstract: Pine polyphenols (PPs) are bioactive dietary constituents that enhance health and help prevent diseases through antioxidants. Antioxidants reduce the level of oxidative damages caused by ionizing radiation (IR). The main purpose of this paper is to study the protective effect of PPs on peripheral blood, liver and spleen injuries in mice induced by IR. ICR (Institute of Cancer Research) male mice were administered orally with PPs (200 mg/kg b.wt.) once daily for 14 consecutive days prior to 7 Gy γ-radiations. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…Ionizing radiation induced the cells to produce excessive ROS, which leads to lipid peroxidation, breaks redox homeostasis within cells and living tissues, generates MDA, and decreases the activities of enzymatic and non-enzymatic antioxidants in vivo [ 26 , 27 , 28 ]. In the present study, as shown in Table 3 , administration of PP and PPM reduced the levels of MDA and restored the SOD activity of irradiated mice, which is consistent with a previous study that showed PP could reduce the redox imbalance and lipid peroxidation, and partly restore the redox balance of radiation-injured mice [ 21 ]. Many other studies also suggested that plant polyphenols had an anti-radiation and anti-oxidative stress effect by restoring the redox balance of the system [ 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Ionizing radiation induced the cells to produce excessive ROS, which leads to lipid peroxidation, breaks redox homeostasis within cells and living tissues, generates MDA, and decreases the activities of enzymatic and non-enzymatic antioxidants in vivo [ 26 , 27 , 28 ]. In the present study, as shown in Table 3 , administration of PP and PPM reduced the levels of MDA and restored the SOD activity of irradiated mice, which is consistent with a previous study that showed PP could reduce the redox imbalance and lipid peroxidation, and partly restore the redox balance of radiation-injured mice [ 21 ]. Many other studies also suggested that plant polyphenols had an anti-radiation and anti-oxidative stress effect by restoring the redox balance of the system [ 29 , 30 , 31 ].…”
Section: Resultssupporting
confidence: 92%
“…Whole-body radiation can damage the mouse digestive system, immune system, and hematopoietic system, causing weight loss in mice [ 21 ]. PP and PPM reduced the decline in body weight, which indicated they may play a radioprotective effect.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In previous study, Li et al . reported that “Pine polyphenols of Pinus koraiensis inhibit damages insulted by radiation in mice,”[ 7 ] the mixture of pine polyphenols was purified from cone of P. koraiensis . Yun and Wang reported “Antioxidant activities of poly phenols from P. korainsis in vitro ,” the extract was prepared from P. koraiensis bark.…”
Section: Introductionmentioning
confidence: 99%